Role of the L1 in FL classrooms: learner and teacher beliefs, attitudes, and practices - Samadi, Mohammad Rahim (Kansas State University, 2011)
The role of first language (L1) has been controversial in foreign language (FL) learning and teaching. This study examines the relationship between L1 use and gender and level of education of EFL teachers as well as gender and EFL proficiency level of learners in an Afghan university setting. It also investigates the relationship between FL use and learner anxiety by learner gender and EFL proficiency level. The study hypothesized that female FL teachers use the L1 more than male teachers in FL classrooms. Second, low FL proficiency learners consider L1 use as necessary in FL classrooms. Third, low FL proficiency students experience more anxiety with the exclusive use of FL than higher level learners. Fourth, female learners experience more anxiety than male students with the exclusive use of FL by learners and teachers. Twenty EFL teachers participated in the study by completing a 19-item questionnaire and sixty EFL learners by completing a 27-item questionnaire about their views towards L1/FL use and learner anxiety. The data, analyzed through SPSS software, included calculating frequencies and percentages, computing correlations, and conducting independent-samples t-tests to compare the mean difference between the variables. The first hypothesis was not supported as male teachers reported using the L1 more than female teachers. The study also revealed that male teachers with BA and MA degrees used the L1 more than female teachers with BA degrees. In contrast, female teachers with MA degrees used the L1 more than male teachers with BA and MA degrees and also more than female teachers with BA degrees. The results supported hypothesis two. More elementary learners considered the use of L1 as necessary than intermediate and advanced students. The findings also supported hypotheses three and four. Elementary learners as well as female students experienced more anxiety with the exclusive use of FL than intermediate and advanced level students and male learners. The principal conclusion indicated a significant positive correlation between the exclusive use of FL and learner anxiety.
Keywords: L1 use; FL use; Learner anxiety; FL proficiency level; Gender; Education level; Foreign Language Instruction (0444)